2016
DOI: 10.1557/jmr.2016.105
|View full text |Cite
|
Sign up to set email alerts
|

Band structure and transport studies of half Heusler compound DyPdBi: An efficient thermoelectric material

Abstract: The discovery of Heusler alloys has revolutionized the research field of intermetallics due to the ease with which one can derive potential candidates for multifunctional applications. During recent years, many half Heusler alloys have been investigated for their thermoelectric properties. The f electron based rare earth ternary half Heusler compound DyPdBi has its f energy levels located close to the Fermi energy level. Other research efforts have emphasized that such materials have good thermoelectric capabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The figure of merit (ZT) intrinsically evaluates the performance of a thermoelectric material and its ability to efficiently generate electrical energy from a thermal source (in this case waste heat). Materials with a ZT close to or greater than unity are suitable and sufficient choices for suitable thermoelectric applications [52]. ZT is given by the relationship:…”
Section: Transport Propertiesmentioning
confidence: 99%
“…The figure of merit (ZT) intrinsically evaluates the performance of a thermoelectric material and its ability to efficiently generate electrical energy from a thermal source (in this case waste heat). Materials with a ZT close to or greater than unity are suitable and sufficient choices for suitable thermoelectric applications [52]. ZT is given by the relationship:…”
Section: Transport Propertiesmentioning
confidence: 99%
“…The half metallic ferromagnet shows semiconducting behavior for electrons of one spin orientation while metallic for electrons with the opposite spin. The emerging new physical properties such as thermoelectricity [75][76][77][78] , superconductivity [79][80][81][82][83] , magnetic ordering 84,85 and topological transitions [86][87][88][89] of HH alloys have attracted more attention.…”
Section: A Structural Descriptionmentioning
confidence: 99%
“…Sportouch et al [ 13 ] measured the TE properties of RNiSb (R = Ho, Er, Tm, Yb, and Y) and observed that their thermopower values range from 21 to 160 μV K −1 whereas the thermal conductivity was in a reasonable range from 3 to 7.5 W m −1 K −1 . Krishnaveni et al [ 14 ] conducted BS and transport studies of HH compound DyPdBi and predicted its potential as an efficient TE material. Skolozdra et al [ 15 ] studied the magnetic and transport properties of RNiSb compounds (R = Gd, Tb, Dy, Yb, and Lu).…”
Section: Introductionmentioning
confidence: 99%